2021
DOI: 10.1097/yic.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and philosophical considerations for the around-the-clock use of scheduled melatonin to promote sedation and reduce aggression in individuals with serious mental illness: a case report

Abstract: Melatonin, the endogenous hormone that helps maintain circadian rhythm, has been used exogenously for both primary and secondary sleep disorders. While the effects of melatonin given prior to planned sleep and to restore normal circadian sleep phases have been well studied, there is little information on the use of melatonin as a pharmacotherapeutic intervention for around-the-clock sedation to prevent agitation and aggressive patient behaviors. This is the first case report to our knowledge of melatonin used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…clozapine, risperidone and quetiapine), decreased the total Yale Brown Obsessive–Compulsive Scale scores (Y-BOCS, P = 0.001) and Positive and Negative Syndrome Scale scores (PANSS, P = 0.03) [ 110 ]. Melatonin, the endogenous hormone that regulates circadian rhythms, is used exogenously for the treatment of sleep disorders [ 111 ]. Available evidence has suggested that melatonin is linked to SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…clozapine, risperidone and quetiapine), decreased the total Yale Brown Obsessive–Compulsive Scale scores (Y-BOCS, P = 0.001) and Positive and Negative Syndrome Scale scores (PANSS, P = 0.03) [ 110 ]. Melatonin, the endogenous hormone that regulates circadian rhythms, is used exogenously for the treatment of sleep disorders [ 111 ]. Available evidence has suggested that melatonin is linked to SCZ.…”
Section: Discussionmentioning
confidence: 99%